Exploring impulse buying in millennial consumers during the COVID-19 pandemic - Smith, Bethany (2022)
This investigation builds upon previous literature exploring impulse purchasing, which has often sampled the millennial consumer group. However, the problem in this research is that it may now be considered outdated as little has specifically analysed this phenomenon since the COVID-19 pandemic; this external event is theorised to have produced such effects as to potentially lead to new information which literature had previously not found. This project views the topic through a constructivist lens, using in-depth interviews to gather rich data which is then interpreted by the researcher to extract deeper meanings and implicit information, which may not be openly revealed due to the potentially sensitive nature of the topic in question. The major findings relate to the distinction in responses between participants from individualist (Western) and collectivist (Eastern) cultures, as well as boredom being exposed as an impulse buying trigger not previously acknowledged in literature. As per the literature review, negative emotions were consolidated as a primary impulse purchasing trigger. The study also identified various impulse purchasing restraints, an area which is not specifically discussed in literature. The millennial consumer group maintain similar responses across the age range, with culture a defining factor in both previous impulse purchasing habits and impulse purchasing responses after the pandemic. The findings confirmed that previous findings relating to the influence of consumer mood states holds true in the COVID-19 world, with the investigation delving deeper into the emotional factors to differentiate between the need for comfort, seeking release, alleviating boredom and stimulating activity, experimentation and productivity. The research also identified various novel findings which were not found in the literature review, namely the notion of impulse buying in relation to gift-giving, the distinction between fulfilment and self-fulfilment and the influence of other shoppers’ habits. The study ends with limitations and managerial implications.